Commensal-bacteria-derived butyrate promotes the T-cell-independent IgA response in the colon. (20th December 2019) - Isobe, Junya; Maeda, Shintarou; Obata, Yuuki; Iizuka, Keito; Nakamura, Yutaka; Fujimura, Yumiko; Kimizuka, Tatsuki; Hattori, Kouya; Kim, Yun-Gi; Morita, Tatsuya; Kimura, Ikuo; Offermanns, Stefan; et al.
Abstract: Secretory immunoglobulin A (SIgA), the most abundant antibody isotype in the body, maintains a mutual relationship with commensal bacteria and acts as a primary barrier at the mucosal surface. Colonization by commensal bacteria induces an IgA response, at least partly through a T-cell-independent process. However, the mechanism underlying the commensal-bacteria-induced T-cell-independent IgA response has yet to be fully clarified. Here, we show that commensal-bacteria-derived butyrate promotes T-cell-independent IgA class switching recombination (CSR) in the mouse colon. Notably, the butyrate concentration in human stools correlated positively with the amount of IgA. Butyrate up-regulated the production of transforming growth factor β1 and all- trans retinoic acid by CD103 + CD11b + dendritic cells, both of which are critical for T-cell-independent IgA CSR. This effect was mediated by G-protein-coupled receptor 41 (GPR41/FFA3) and GPR109a/HCA2, and the inhibition of histone deacetylase. The butyrate-induced IgA response reinforced the colonic barrier function, preventing systemic bacterial dissemination under inflammatory conditions. These observations demonstrate that commensal-bacteria-derived butyrate contributes to the maintenance of the gut immune homeostasis by facilitating the T-cell-independent IgA response in the colon. Abstract : Butyrate conditions DCs to promote IgA production in the gut